2016
DOI: 10.1016/j.imr.2016.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Bodily differences between Cold- and Heat-prescription groups in Sasang medicine

Abstract: BackgroundIn Sasang medicine, patients are treated with herbal prescriptions based on Cold-Heat patterns induced by conditions of physiological equilibrium among internal organs, which also induce differences in body circumferences. The objective of the current study was to elucidate the relationship between Cold- and Heat-prescription types and body circumferences.MethodsData from suitable subjects (115 males and 222 females) were collected, and the body circumferences were compared according to their Cold- a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 10 publications
1
10
0
Order By: Relevance
“…Interestingly, the results of this study are consistent with TKM theory [ 30 ]. Although there are no previous studies examining tongue color, a comparative study was conducted on the facial color of patients with cold and heat patterns in the Tae-Eum type by Park YJ et al [ 31 ]. They observed that facial colors based on actual clinical data were similar among three types (Tae-Eum, So-Yang, and So-Eum).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the results of this study are consistent with TKM theory [ 30 ]. Although there are no previous studies examining tongue color, a comparative study was conducted on the facial color of patients with cold and heat patterns in the Tae-Eum type by Park YJ et al [ 31 ]. They observed that facial colors based on actual clinical data were similar among three types (Tae-Eum, So-Yang, and So-Eum).…”
Section: Discussionmentioning
confidence: 99%
“…As for the body shape, Heat subgroups of Tae-Eum and So-Yang type have higher BMI value than Cold subgroups in this study ( Table 3 ). In a previous study with So-Yang and Tae-Eum types 29 , Heat subgroup was higher than Cold subgroup in the chest circumference of So-Yang male and rib-to-pelvic circumference ratio of Tae-Eum type, although the BMI showed no significant differences between Cold and Heat prescription subgroups. However, other study without considering Sasang typology showed that the BMI of Heat pattern group is higher than that of Cold pattern group in male and female 33 .…”
Section: Discussionmentioning
confidence: 56%
“…One study examined the pathophysiological features of Cold-Heat subgroups with arbitrary measures lacking quantification and validation 27 , 28 . Another study examined the temperament of subgroups using only the So-Yang type groups 25 , and body shape with two Sasang type groups of Tae-Eum and So-Eum 29 .…”
Section: Introductionmentioning
confidence: 99%
“…Attempts have been made to quantitatively analyze the complexion to use this important factor objectively in TKM diagnoses [ 10 ]. One study examined the use of the complexion as a diagnostic element in SCM, in addition to body shape or symptoms [ 11 , 12 ]. Although some studies have examined the use of the complexion as a diagnostic factor, objective evidence based on clinical data has been insufficient.…”
Section: Introductionmentioning
confidence: 99%